AWARENESS REGARDING USE OF LINING UNDER POSTERIOR COMPOSITE RESTORATIONS AMONG GENERAL DENTISTS OF LAHORE - Khan, Salman Ashraf; Bajwa, Obaid; Khalid, Naima; Khan, Nissa (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate awareness among the General Dentists of Lahore regarding the use of lining materials under posterior resin restorations.Study Design: Cross-sectional study.Place and Duration of Study: The study was conducted in Lahore, from Sep 2019 to Jan 2020.Methodology: Non-probability consecutive sampling technique was used. A sample size of 271 was calculated. The questionnaires were distributed by 2 surveyors to the general dentists of Lahore, Pakistan.Results: The response rate was 100%. Amongst these dentists, 191 (63.87%) affirmed that they use lining materials in initial depth cavities, 248 (82.94%) used lining material under moderate depth restorations and 285 (95.31%) used lining materials under advanced depth cavities with calcium hydroxide being the most commonly used material.Conclusion: The findings of the present study indicate that general dentists of Lahore are unaware of the contemporary concepts regarding the placement of cavity liners and tend to place liners in initial and moderate depth cavities under posterior resin restorations.